Hexokinase Domain Containing 1 (HKDC1) Gene Variants and their Association with Gestational Diabetes Mellitus in a South Indian Population. (July 2016) - Kanthimathi, Sekar; Liju, Samuel; Laasya, Dhandapani; Anjana, Ranjit Mohan; Mohan, Viswanathan; Radha, Venkatesan
Summary: Hexokinase domain containing 1 ( HKDC1 ), a novel human hexokinase gene, is known to affect glucose metabolism and was shown to have a strong association with 2‐h plasma glucose in pregnant women in a recent genome wide association study. This study aimed to evaluate the association of these regulatory variants of HKDC1 (rs1076224, rs4746822, rs2394529 and rs9645501) with gestational diabetes mellitus (GDM) in a South Indian population. The regulatory variants of HKDC1 were genotyped in unrelated 500 women with GDM and 510 non‐GDM individuals by using the MassARRAY system and by direct DNA sequencing. The minor alleles of the HKDC1 gene regulatory variants, namely rs10762264 and rs4746822, showed a significant association with GDM and these alleles conferred as much as 1.24 and 1.34 times higher risk for GDM, respectively. This is the first study to demonstrate the association of HKDC1 genetic variants with susceptibility to GDM.